2014
DOI: 10.1108/jic-03-2013-0034
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual capital reporting: a longitudinal study of New Zealand companies

Abstract: Purpose – The purpose of this paper is to examine intellectual capital reporting patterns of New Zealand companies over a longitudinal period, comparing knowledge intensive companies with traditional product-based companies. Design/methodology/approach – Content analysis was used to examine the intellectual capital reporting of five knowledge intensive companies and five traditional product-based companies listed on the New Zealand Stock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 22 publications
1
45
1
2
Order By: Relevance
“…Previous ICD studies consistently showed that HCD in annual reports was predominantly disclosed after relational capital disclosure (RCD) (e.g., Guthrie & Petty 2000;Brennan 2001;Bozzolan, O' Regan & Ricceri 2006;Campbell & Rahman 2010;Abhayawansa & Azim 2014). However, several other recent studies (e.g., Wagiciengo & Belal 2012;Bellora & Guenther 2013;De Silva, Stratford & Clark 2014). The results of these studies may reflect the expanding interest on reporting human capital over relational and structural capital information.…”
Section: Introductioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Previous ICD studies consistently showed that HCD in annual reports was predominantly disclosed after relational capital disclosure (RCD) (e.g., Guthrie & Petty 2000;Brennan 2001;Bozzolan, O' Regan & Ricceri 2006;Campbell & Rahman 2010;Abhayawansa & Azim 2014). However, several other recent studies (e.g., Wagiciengo & Belal 2012;Bellora & Guenther 2013;De Silva, Stratford & Clark 2014). The results of these studies may reflect the expanding interest on reporting human capital over relational and structural capital information.…”
Section: Introductioncontrasting
confidence: 52%
“…The findings suggested that human capital was the second most popular information disclosed (after relational capital) and accounted for 30% of the total ICD. Many subsequent studies followed the similar genre of Guthrie and Petty (2000) Silva et al 2014 in New Zealand) used corporate annual reports as the study subject. In the Malaysian context, similar studies were conducted by Haji and Ghazali (2012) and Amin, Saringat, Hassan and Ismail (2013).…”
Section: Previous Studies On Hcdmentioning
confidence: 99%
“…In the first stream, several longitudinal studies show that the companies increased their level of IC disclosure over time (Abdolmohammadi, 2005;Vergauwen et al, 2007;Wagiciengo and Belal, 2012;De Silva et al, 2014). Other studies have examined the types of IC information disclosed by companies to investigate whether they are quantitative (numerical) or rather qualitative (descriptive/narrative) in nature.…”
Section: Ic Disclosurementioning
confidence: 99%
“…Different studies that considered industry as an independent variable of ICD have shown different results. De Silva et al (2014) and Branco et al (2011) have not found industry as determinant of ICD. However for Cordazzo (2007), Oliveira et al (2006) and Whiting and Woodcock (2011) industry has appeared to be a significant determinant of ICD.…”
Section: Stakeholders" Pressurementioning
confidence: 99%